2022
DOI: 10.3390/cancers14205115
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Trastuzumab

Abstract: One of the most impactful biologics for the treatment of breast cancer is the humanized monoclonal antibody, trastuzumab, which specifically recognizes the HER2/neu (HER2) protein encoded by the ERBB2 gene. Useful for both advanced and early breast cancers, trastuzumab has multiple mechanisms of action. Classical mechanisms attributed to trastuzumab action include cell cycle arrest, induction of apoptosis, and antibody-dependent cell-mediated cytotoxicity (ADCC). Recent studies have identified the role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 214 publications
0
32
0
Order By: Relevance
“…Our results are in line with previous reports suggesting that metabolic rewiring may contribute to Tz resistance. In particular, previous studies showed that fatty acid metabolism, membrane lipid rafts, and ERBB2 pathogenesis have close relationships [16] and that Tz increases lipogenesis via FAS promoter [29]. Furthermore, a previous study showed that lapatinib-resistant cells undergo a CD63-mediated rewiring of the lipid metabolism [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results are in line with previous reports suggesting that metabolic rewiring may contribute to Tz resistance. In particular, previous studies showed that fatty acid metabolism, membrane lipid rafts, and ERBB2 pathogenesis have close relationships [16] and that Tz increases lipogenesis via FAS promoter [29]. Furthermore, a previous study showed that lapatinib-resistant cells undergo a CD63-mediated rewiring of the lipid metabolism [30].…”
Section: Discussionmentioning
confidence: 99%
“…ERBB2 was found downregulated in Tz-R MDA-MB-361. As downregulation of ERBB2 after Tz therapy has been observed in vitro and in vivo and this may promote resistance toward Tz [16,25], we evaluated whether this mechanism was present in all our Tz-R cell models at the level of the plasma membrane [PM] where ERBB2 plays his main role. FCM analysis with the Tz antibody used to detect ERBB2, revealed that MDA-MB-361 Tz-R displayed a robust and statistically significant decrease in the levels of ERBB2 exposed on their PM.…”
Section: Generation and Characterization Of Erbb2+ Tz-r Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…VM is a recent concept describing tumor vascular pattern used by many tumors, particularly glioblastoma. The process of VM includes the transition of tumor cells into a vascular phenotype forming tube structure and expressing endothelial surface antigens such as VE-cadherin and EphA2 as well as periodic acid-Schiff (PAS) 15 . The endothelial-like characteristics deployed by the tumor cells ensure their control of the tumor nutrient supply and their metabolic adaptation to resist the immune system assault and anti-angiogenic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Even though trastuzumab has been proven to be efficient in the treatment of HER2+ breast cancer, as it was mentioned before, resistance events impair its therapeutic effect [ 15 , 16 ]. Several trastuzumab resistance mechanisms have been described in the literature [ 36 , 37 ]. In particular, one of the described mechanisms of resistance is the expression of the membrane glycoprotein mucin 4 (MUC4), which masks the trastuzumab-binding epitope on the HER2 molecule [ 38 ].…”
Section: Her2-targeted Therapiesmentioning
confidence: 99%